Association Between New Unconfirmed Bone Lesions and Outcomes in Men With Metastatic Castration-Resistant Prostate Cancer Treated With Enzalutamide: Secondary Analysis of the PREVAIL and AFFIRM Randomized Clinical Trials - Armstrong, Andrew J. (JAMA Oncol, 2019)
IMPORTANCE: For men with metastatic castration-resistant prostate cancer (mCRPC) whose condition is responding to enzalutamide, new unconfirmed bone lesions detected at posttreatment scinitigraphy may reflect an osteoblastic reaction that represents healing, known as pseudoprogression, which can lead to premature discontinuation of therapy. OBJECTIVE: To determine the association between new unconfirmed lesions detected on a follow-up bone scintigram (bone scan) and outcomes in enzalutamide-treated men with mCRPC. DESIGN, SETTING, AND PARTICIPANTS: This post hoc, retrospective secondary analysis of 1672 enzalutamide-treated men from 2 phase 3, randomized mCRPC studies (PREVAIL and AFFIRM) before or after treatment with docetaxel was conducted from April 12, 2018, to July 25, 2019. Participants were men from the enzalutamide groups of the 2 studies with a decrease in prostate-specific antigen level at any time or with stable disease or soft-tissue disease responding to treatment based onradiologic findings. INTERVENTION: Enzalutamide, 160 mg once daily. MAIN OUTCOMES AND MEASURES: The clinical significance of new lesions detected on the first (early) or second (late) posttreatment bone scan, without an unfavorable change in prostate-specific antigen level or soft-tissue progression, was investigated. Associations of new unconfirmed lesions with radiographic progression-free survival, overall survival, decrease in prostate-specific antigen level, objective response in soft tissue, and quality of life were evaluated. RESULTS: Among the 643 men (median age, 72 years [range, 43-93 years]) in PREVAIL, early and late unconfirmed lesions were observed in 177 men (27.5%) with stable disease or disease responding to enzalutamide. Among the 404 men (median age, 70 years [range, 41-88 years]) in AFFIRM, early and late unconfirmed lesions were observed in 73 men (18.1%) with stable disease or disease responding to enzalutamide. In PREVAIL, men with new unconfirmed lesions had median radiographic progression-free survival (hazard ratio [HR], 1.37 [95% CI, 0.81-2.30]; P = .23) and median overall survival (HR, 1.25 [95% CI, 0.85-1.83]) in the chemotherapy-naive setting similar to men those of men without such new lesions. In AFFIRM, the median overall survival (HR, 1.94 [95% CI, 1.10-3.44]) was reduced among men with unconfirmed bone lesions, but the median radiographic progression-free survival was not reduced (HR, 1.21 [95% CI, 0.83-1.75]; P = .32). Quality of life over time was similar regardless of the presence of new unconfirmed lesions detected on a follow-up bone scan in either setting. CONCLUSIONS AND RELEVANCE: These results suggest that new unconfirmed lesions detected on follow-up bone scans may represent pseudoprogression in men with mCRPC and are indicative of a favorable treatment response to enzalutamide. The detection of new unconfirmed bone lesions in men with mCRPC that responded to treatment with enzalutamide after docetaxel appears to be associated with worse overall survival and may represent true progression, thus highlighting the need for improved functional bone metastasis imaging. TRIAL REGISTRATION: ClinicalTrials.gov Identifiers: NCT01212991 and NCT00974311